From Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) - post-ISDC review revised proposal - Baum, Michael; Al-Zu'bi, Maha (2023)
CGIAR Initiative on Fragility to Resilience in Central and West Asia and North Africa (F2R-CWANA) proposal for 2022-2025 (Q1) business cycle, revised from original submission based on ISDC feedback.